Oxidative Stress and Insulin Resistance Among Polycystic Ovary Syndrome Patients. A Cross-Sectional Study In Makassar, Indonesia - Resnawaldi, Arlen; Abdullah, Nusratuddin; Rambulangi, Samrichard; Kasim, Firdaus; Fujiko, Masita; Malinta, Umar (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to know the relationship between levels of oxidative stress and the incidence of insulin resistance in patients with Polycystic Ovary Syndrome (PCOS). This is an observational study with a cross-sectional approach. Samples of 27 patients with insulin resistance confirmed by IR HOMA > 2 and 27 patients without insulin resistance confirmed by HOMA IR < 2, then all subjects were tested for reactive oxygen species (ROS) levels using the enzyme-linked immunosorbent assay (ELISA) method from January to December 2019. The average level of reactive oxygen species (ROS) was 1.58, and the average value of HOMA-IR was 2.91. There was a significant relationship between the ROS levels and the value of HOMA IR in patients with Polycystic Ovary Syndrome (PCOS) (p = 0.001; p <0.05). This study concludes that a significant relationship between ROS and insulin resistance (HOMA-IR) is based on the mechanism of hyperglycemia due to insulin resistance resulting in an increase in reactive oxygen species (ROS), which results in hyperandrogenic conditions in patients with Polycystic Ovary Syndrome (PCOS).